The influence of digital leadership on employee performance through digital culture and innovation work behavior at Bank Indonesia - Rahayu Azi; Justine Tanuwijaya; Andreas Wahyu Gunawan (Institute of Computer Science (IOCS), 2024)
This research examines the impact of digital leadership on employee performance through digital culture and innovation work behavior at Bank Indonesia. Utilizing a quantitative approach with data collected from Bank Indonesia Head Office employees, the study employs structural equation modeling for analysis. Findings indicate a positive influence of digital leadership on digital culture and innovation work behavior. However, digital leadership does not directly affect employee performance but can be mediated through innovation work behavior. Both digital culture and innovation work behavior significantly impact employee performance. Notably, digital leadership's influence on employee performance is moderated by innovation work behavior. This research sheds light on the intricate dynamics between digital leadership, organizational culture, innovation, and employee performance, providing valuable insights for organizational development strategies